Sports as Medium for Counselling Guidance for Student Mental Health: case study in Higer education 4 Takengon - Nopri Abadi Miko; Birrul Walidaini; Rizky Bintang Setiawan (Borneo Novelty Publishing, 2025)
Purpose- This study aims to describe the role of sports activities in improving students' mental health through Guidance and Counselling services at Takengon 4th State Senior High School. Research Methodology / Design / Approach-A qualitative approach with descriptive methods was used. The research subjects included guidance counsellors, physical education teachers, the principal, and students selected using purposive sampling techniques. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources, techniques, and member checks. Finding- The results showed that sports activities had a significant positive impact on students' mental health, particularly in reducing stress and anxiety and increasing self-confidence. Guidance and counselling services act as facilitators by integrating sports activities into student development programmes to support psychological well-being. Originality/Value-The synergy between sports and guidance and counselling services creates a more conducive learning environment, builds social skills, and reinforces positive values such as discipline and cooperation. Thus, sports activities integrated with guidance and counselling services are an effective strategy for improving students' mental health.